A study on adapting tasks in English 7 on the basis of communicative language teaching for students at Minh Khai secondary school, Hoai Duc, Ha Noi = Nghiên cứu về việc điều chỉnh các hoạt động trong sách giáo khoa tiếng Anh 7 theo hướng giao tiếp cho học - Nguyễn, Thị Nga (ĐHNN, 2017)
42 p. + CD-ROM